Balanced Scorecard: Weaknesses, Strengths, and its Ability as Performance Management System Versus other Performance Management Systems - Salem, Milad Abdelnabi; Hasnan, Norlena; Osman, Nor Hasni
Since the last decades, the performance management has become a legislative requirement for the private and public sectors. Companies are looking to find the tool that a can measure the performance effectively. One of the attractive areas subject to be measured is the social and environmental considerations. This paper provides theoretical discussion of the BSC and compares it with other different measurement systems. Moreover, it evaluates the ability of BSC to incorporate the social and environmental issues. The paper concluded that although the criticisms of BSC, it has many advantages versus other performance systems. It also strongly suggested the ability to BSC to incorporate the social and environmental issues, which can open the door for coming studies to consider such issue